(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
List of textbooks and study guides, recommendations on topics in science teaching, introduction and main parts, practical workshops and experiments. Based on the requirements of the state educational standards, it is possible to provide a drawing, course work and projects, as well as their topics and directions, from certain subjects. Hours allocated to topics, didactic and technical tools used for topics, types of knowledge control for topics and sections, and appropriate methodological recommendations should be clearly indicated.